Proactively Pivot: Guidance on Adapting the PBIS Framework in Response to Crises to Support Students With Disabilities. (September 2022) - Clemens, Katharine; Borowski, Luke; Donovan, Mary; Meyer, Katherine; Dooley, Kathryn; Simonsen, Brandi
Schools that employ evidence-based multi-tiered system of supports (MTSS) frameworks, like Positive Behavioral Interventions and Supports (PBIS), invest in core system, data, and practice features to support students, families, and educators. A strong framework enables settings to enhance and adjust their implementation to meet the needs of all students, including students with disabilities, in a range of contexts. Importantly, as schools pivoted among remote, hybrid, and in-person learning modes throughout 2020 and 2021, effective leadership teams used their PBIS framework to successfully navigate these transitions. Based on lessons learned during this period, we present three key recommendations to adapt implementation in response to crises: (1) leverage existing systems, (2) use data to guide decision-making, and (3) pivot practices. To illustrate these recommendations, we describe PBIS implementation in an alternative setting supporting students with disabilities and share examples of how educators used the PBIS framework to meet the challenges presented by new contexts.